Effect of Mean Annual Changeability of Air Temperature, Surface Ozone Concentration and Galactic Cosmic Rays Intensity on the Mortality of Tbilisi City Population - Amiranashvili, Avtandil G.; Bakradze, Teimuraz S.; Berianidze, Nino T.; Japaridze, Nino D.; Khazaradze, Ketevan R. (Journals of Georgian Geophysical Society, 2017)
The results of a study of the effect of the annual changeability of air temperature, surface ozone concentration and and neutron component of galactic cosmic rays intensity on the mortality of the population of Tbilisi city in 1984-2010 are presented. The statistical characteristics of the investigated time-series are studied. In particular, it was found that within the variation range the contribution of the studied parameters to mortality variability is as follows: a random component of air temperature - 8.5%, real values ​​of surface ozone concentration and cosmic ray intensity - 20.9% and 16.5%, respectively.